1987
DOI: 10.1007/bf01533761
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the steroid and prolactin concentration in follicular fluid and the maturation and fertilizaton of human oocytes

Abstract: Seventy-eight follicles and their follicular fluid were aspirated from 46 women undergoing in vitro fertilization (IVF) procedures after stimulation of the ovaries with a low-dose human menopausal gonadotropin/human chorionic gonadotropin stimulation regimen. The concentrations of estradiol (E2), progesterone (P), testosterone (T), and prolactin (PRL) were measured in follicular fluid and related to the maturation of the oocyte-corona-cumulus complex (OCCC) and the fertilization of oocytes. Follicles containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…A similar situation exists in the population of small follicles during the luteal phase of normally cycling women (30). A comparable pattern of steroid levels in follicular fluid has been noted in follicles yielding either immature or failed fertilization oocytes in gonadotropin-stimulated cycles (31). Taken together, the steroidogenic pattern of type A cumulus cells resembles the steroidogenic pattern of growing follicles and, to some extent, small follicles.…”
Section: Discussionsupporting
confidence: 56%
“…A similar situation exists in the population of small follicles during the luteal phase of normally cycling women (30). A comparable pattern of steroid levels in follicular fluid has been noted in follicles yielding either immature or failed fertilization oocytes in gonadotropin-stimulated cycles (31). Taken together, the steroidogenic pattern of type A cumulus cells resembles the steroidogenic pattern of growing follicles and, to some extent, small follicles.…”
Section: Discussionsupporting
confidence: 56%
“…It reflects the metabolism of the whole follicle, contains regulatory molecules that are crucial for the successful maturation of oocytes, and is a byproduct of oocyte retrieval, all of which make it an ideal candidate for development as an noninvasive oocyte selection method. Previous studies have looked at the concentration of various hormones (8)(9)(10)(11)(12), growth factors (13)(14)(15)(16)(17), and reactive oxygen species (18)(19)(20) in human follicular fluid and have tried with limited success to relate it to fertilization rate, oocyte developmental potential, and pregnancy outcome. Targeted analysis of certain amino acids has revealed interesting correlations with IVF outcomes in human studies (21)(22)(23).…”
mentioning
confidence: 99%
“…Reinthaller et al (30,31) found an inverse correlation between follicular PRL levels and oocyte maturation. The more mature oocytes have lower levels of PRL and higher levels of P, T, and E 2 at the time of egg retrieval.…”
Section: Figurementioning
confidence: 97%
“…The more mature oocytes have lower levels of PRL and higher levels of P, T, and E 2 at the time of egg retrieval. Reinthaller et al (30,31) hypothesize that PRL inhibits the aromatization of androgens to estrogens in counterpoint to FSH stimulatory effects. PRL appears to exert a regulatory influence upon the estrogen-androgen metabolism in granulosa cells within the developing follicle, specifically on the aromatase enzyme.…”
Section: Figurementioning
confidence: 98%